Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write Berbantuan Media Flashcard Terhadap Kemampuan Menulis Teks Deskriptif Siswa Sekolah Dasar - Ghina Nur’aini; Dadan Setiawan; Idah Faridah Laily (Journal of Humanities, Social Sciences, and Education, 2025)
This research was prompted by the low ability of fifth-grade students at SD Negeri Cipicung to write descriptive texts in English, stemming from difficulties in sentence construction, limited vocabulary, and a lack of understanding of descriptive text structure, further exacerbated by conventional teaching methods and minimal use of media. To address these issues, the Think Talk Write (TTW) cooperative learning model, assisted by flashcard media, was employed to determine its influence on students' writing ability, describe its implementation, and measure the effectiveness and improvement of student learning outcomes. Utilizing a quantitative, quasi-experimental design involving an experimental class with the TTW model and a control class with conventional methods, data analysis via independent sample t-test and N-Gain test revealed that the TTW model assisted by flashcards significantly improved students' writing ability, with a significance value of 0.008 (< 0.05) and an average N-Gain of 68.38% (moderately effective), thus making it a suitable strategy for teaching English writing in elementary schools